The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.2528/pier13121310
|View full text |Cite
|
Sign up to set email alerts
|

Classification of Alzheimer Disease Based on Structural Magnetic Resonance Imaging by Kernel Support Vector Machine Decision Tree

Abstract: Abstract-In this paper we proposed a novel classification system to distinguish among elderly subjects with Alzheimer's disease (AD), mild cognitive impairment (MCI), and normal controls (NC). The method employed the magnetic resonance imaging (MRI) data of 178 subjects consisting of 97 NCs, 57 MCIs, and 24 ADs. First, all these three dimensional (3D) MRI images were preprocessed with atlas-registered normalization. Then, gray matter images were extracted and the 3D images were under-sampled. Afterwards, princ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
77
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 187 publications
(78 citation statements)
references
References 36 publications
1
77
0
Order By: Relevance
“…When λ equals zero, the objective function reduces to the squared error version of non-negative matrix factorization (NMF) [25]. The form of ξ defines how sparseness is measured, and it is suggested that a typical choice for ξ is ξ(H kj ) = |H kj | in [11].…”
Section: Non-negative Sparse Codingmentioning
confidence: 99%
See 1 more Smart Citation
“…When λ equals zero, the objective function reduces to the squared error version of non-negative matrix factorization (NMF) [25]. The form of ξ defines how sparseness is measured, and it is suggested that a typical choice for ξ is ξ(H kj ) = |H kj | in [11].…”
Section: Non-negative Sparse Codingmentioning
confidence: 99%
“…Thus, completely non-negative sparse coding have been investigated in [23]. Recently, NNSC has emerged as a useful feature extraction method in areas related to face recognition and image denoising [24,25]. In this work, non-negative T -F representations has been applied to target HRR profiles to obtain non-negative T -F data matrix, so NNSC is naturally considered for non-negative T -F feature extraction.…”
Section: Introductionmentioning
confidence: 99%
“…Up to date there is no perfect resolution of 3D triangulation in theory and method [3,8,9]. There are four triangulation methods including triangulation growth method, point by point interpolation, merge segmentation method and 3D to 2D projection.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang [43] proposed a novel classification system to distinguish among elderly subjects with AD, MCI, and NC. First, all these three dimensional (3D) MRI images were pre-processed with atlas-registered normalization.…”
Section: Literature Surveymentioning
confidence: 99%